Market segmentation: a vital component of hotel marketing - Evans, Martin (Henry Stewart Talks, 2009)
The role of marketing in the hotel industry, The importance of knowing your customer, Principles of market segmentation, Types of market segments for hotels, How to apply market segmentation, The segment led marketing plan